2016
DOI: 10.1589/jpts.28.1368
|View full text |Cite
|
Sign up to set email alerts
|

The antalgic effects of non-invasive physical modalities on central post-stroke pain: a systematic review

Abstract: Abstract. [Purpose] This study systematically reviewed the antalgic effects of non-invasive physical modalities (NIPMs) on central post-stroke pain (CPSP). [Subjects and Methods] Clinical studies were sought on September 2015 in 10 electronic databases, including Medline and Scopus. The searching strings were "central pain and stroke" and "treatment, and physical or non-pharmacological". The inclusion and exclusion criteria were set for screening the clinical articles by two reviewers. Pain scores on visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…58 A recent systematic review that included nine HF-rTMS studies suggested an effect on CPSP relief, but also underlined the insufficient quality of the studies considered. 60…”
Section: Introductionmentioning
confidence: 99%
“…58 A recent systematic review that included nine HF-rTMS studies suggested an effect on CPSP relief, but also underlined the insufficient quality of the studies considered. 60…”
Section: Introductionmentioning
confidence: 99%
“…These reduce the pain and induce neuro modulatory effects for motor deficits. These non invasive modalities such as TENS, which have no side effects and easy to operate and inexpensive [17]. However the current stream of treatment for thalamic pain syndrome is by pharmacological interventions , deep brain stimulation , boutlinum toxin , motor cortex stimulation, transcranial magnetic stimulation and caloric vestibular stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 8 , 9 ] The current mainstream treatments are pharmacological in nature. [ 10 ] Several nonpharmacological therapies have also been demonstrated to be effective for patients with CPSP in clinical trials; [ 9 , 11 , 12 ] however, few systematic reviews have summarized their effectiveness and safety. [ 10 , 13 ] Hence, this systematic review was conducted to evaluate the efficacy and safety of nonpharmacological therapies for controlling CPSP, based on scientific evidence.…”
Section: Introductionmentioning
confidence: 99%